Exact and Nonstandard Finite Difference Schemes for Coupled Linear Delay Differential Systems - María Ángeles Castro (Mathematics, 2019)
In recent works, exact and nonstandard finite difference schemes for scalar first order linear delay differential equations have been proposed. The aim of the present work is to extend these previous results to systems of coupled delay differential equations <semantics> X ′ ( t ) = A X ( t ) + B X ( t − τ ) , </semantics> where X is a vector, and A and B are commuting real matrices, in general not simultaneously diagonalizable. Based on a constructive expression for the exact solution of the vector equation, an exact scheme is obtained, and different nonstandard numerical schemes of increasing order are proposed. Dynamic consistency properties of the new nonstandard schemes are illustrated with numerical examples, and proved for a class of methods.